Respuesta :

Answer:

2. cotФ = [tex]-\frac{4}{3}[/tex]

3. sec²Ф - tan²Ф = 1

4. [tex]\frac{sin^{2}\alpha+cos^{2}\alpha}{tan^{2}\alpha+1}[/tex] = cos²∝

5. The value of sin x is [tex]\frac{1}{2}[/tex]

6. cos 15° =  [tex]\frac{\sqrt{6}+\sqrt{2}}{4}[/tex]

7. tan(α + β) = [tex]-\frac{63}{16}[/tex]

8. sin(π - Ф) = sin Ф

9. cos 2Ф = [tex]-\frac{1}{2}[/tex]

10. sin 2Ф = 0.96

Step-by-step explanation:

2.

∵ cos Ф = [tex]-\frac{4}{5}[/tex]

∵ 90° < Ф < 180°

- That means Ф lies on the 2nd quadrant

∴ sin Ф is a positive value

∵ sin²Ф + cos²Ф = 1

∴ sin²Ф + ( [tex]-\frac{4}{5}[/tex] )² = 1

∴ sin²Ф +  [tex]\frac{16}{25}[/tex] = 1

- Subtract from both sides  [tex]\frac{16}{25}[/tex]

∴ sin²Ф =  [tex]\frac{9}{25}[/tex]

- Take √ for both sides

∴ sinФ = [tex]\frac{3}{5}[/tex]

∵ cotФ = cosФ ÷ sinФ

∴ cotФ = [tex]-\frac{4}{5}[/tex] ÷  [tex]\frac{3}{5}[/tex]

cotФ = [tex]-\frac{4}{3}[/tex]

3.

The expression is sec²Ф - tan²Ф

∵ tan²Ф = sec²Ф - 1

- Substitute tan²Ф by the right hand side in the expression

∴ sec²Ф - tan²Ф = sec²Ф - (sec²Ф - 1)

∴ sec²Ф - tan²Ф = sec²Ф - sec²Ф + 1

- Simplify the right hand side

sec²Ф - tan²Ф = 1

4.

The expression is  [tex]\frac{sin^{2}\alpha+cos^{2}\alpha}{tan^{2}\alpha+1}[/tex]

∵ The numerator is sin²∝ + cos²∝

∵ sin²∝ + cos²∝ = 1

∴ The numerator = 1

∵ The denominator is tan²∝ + 1

∵ tan²∝ = [tex]\frac{sin^{2}\alpha}{cos^{2}\alpha}[/tex]

∴ tan²∝ + 1 =  [tex]\frac{sin^{2}\alpha}{cos^{2}\alpha}[/tex] + 1

- Change 1 to  fraction [tex]\frac{cos^{2}\alpha}{cos^{2}\alpha}[/tex]

∴ tan²∝ + 1 =  [tex]\frac{sin^{2}\alpha}{cos^{2}\alpha}[/tex] +  [tex]\frac{cos^{2}\alpha}{cos^{2}\alpha}[/tex]

- Add the two fractions  

∴ tan²∝ + 1 =  [tex]\frac{sin^{2}\alpha+cos^{2}\alpha }{cos^{2}\alpha}[/tex]

∵ sin²∝ + cos²∝ = 1

∴ tan²∝ + 1 = [tex]\frac{1}{cos^{2}\alpha}[/tex]

∴ The denominator =  [tex]\frac{1}{cos^{2}\alpha}[/tex]

∴  [tex]\frac{sin^{2}\alpha+cos^{2}\alpha}{tan^{2}\alpha+1}[/tex] = [tex]\frac{1}{\frac{1}{cos^{2}\alpha}}[/tex]

- Remember denominator the denominator will be a numerator

[tex]\frac{sin^{2}\alpha+cos^{2}\alpha}{tan^{2}\alpha+1}[/tex] = cos²∝

5.

∵ tan x cos x = [tex]\frac{1}{2}[/tex]

∵ tan x = [tex]\frac{sin(x)}{cos(x)}[/tex]

∴ [tex]\frac{sin(x)}{cos(x)}[/tex] × cos x = [tex]\frac{1}{2}[/tex]

- Simplify it by canceling cos x up with cos x down

∴ sin x = [tex]\frac{1}{2}[/tex]

The value of sin x is [tex]\frac{1}{2}[/tex]

6.

∵ cos(Ф - ∝) = cosФ cos∝ + sinФ sin∝

∵ 45 - 30 = 15

∴ cos 15° = cos(45 - 30)°

- Use the rule above to find the exact value

∵ cos(45 - 30)° = cos 45° cos 30° + sin 45° sin 30°

∵ cos 45° = [tex]\frac{\sqrt{2}}{2}[/tex] and sin 45° =

∵ cos 30° = [tex]\frac{\sqrt{3}}{2}[/tex] and sin 30° = [tex]\frac{1}{2}[/tex]

∴ cos(45 - 30)° =  [tex]\frac{\sqrt{2}}{2}[/tex] ×  [tex]\frac{\sqrt{3}}{2}[/tex] +  

∴ cos(45 - 30)° =  [tex]\frac{\sqrt{6}}{4}[/tex] +  [tex]\frac{\sqrt{2}}{4}[/tex]  = [tex]\frac{\sqrt{6}+\sqrt{2}}{4}[/tex]

cos 15° =  [tex]\frac{\sqrt{6}+\sqrt{2}}{4}[/tex]

7.

∵ tan(α + β) = [tex]\frac{tan\alpha+tan\beta}{1-tan\alpha.tan\beta}[/tex]

∵ cos α = [tex]\frac{5}{13}[/tex] and 0° < α < 90°

- That means α is in the 1st quadrant, then all trigonometry

    ratios are positive

∵ sin²α + cos²α = 1

∴ sin²α + ( [tex]\frac{5}{13}[/tex] )² = 1

∴ sin²α + [tex]\frac{25}{169}[/tex]  = 1

- Subtract  [tex]\frac{25}{169}[/tex]  from both sides

∴ sin²α =  [tex]\frac{144}{169}[/tex]

- Take √ for both sides

∴ sin α =  [tex]\frac{12}{13}[/tex]

∵ tan α = sin α ÷ cos α

∴ tan α = [tex]\frac{12}{13}[/tex] ÷ [tex]\frac{5}{13}[/tex]

∴ tan α = [tex]\frac{12}{5}[/tex]  

∵ sin β = [tex]\frac{3}{5}[/tex] and 0° < β < 90°

∵ sin²β + cos²β = 1

∴ ( [tex]\frac{3}{5}[/tex] )² + cos²β = 1

∴ [tex]\frac{9}{25}[/tex] + cos²β = 1

- Subtract  [tex]\frac{9}{25}[/tex]  from both sides

∴ cos²β =  [tex]\frac{16}{25}[/tex]

- Take √ for both sides

∴ cos β =  [tex]\frac{4}{5}[/tex]

∵ tan β = sin β ÷ cos β

∴ tan β = [tex]\frac{3}{5}[/tex] ÷ [tex]\frac{4}{5}[/tex]

∴ tan β = [tex]\frac{3}{4}[/tex]  

- Substitute the values of tan α and tan β in the tan (α + β)

∵ tan(α + β) = [tex]\frac{tan\alpha+tan\beta}{1-tan\alpha.tan\beta}[/tex]

∴ tan(α + β) = [tex]\frac{\frac{12}{5}+\frac{3}{4}}{1-(\frac{12}{5})(\frac{3}{4})}[/tex]

tan(α + β) = [tex]-\frac{63}{16}[/tex]

8.

∵ sin(α - β) = sin α cos β - cos α sin β

∴ sin(π - Ф) = sin π cos Ф - cos π sin Ф

∵ sin π = 0 and cos π = -1

∴ sin(π - Ф) = (0) × cos Ф - (-1) × sin Ф

∴ sin(π - Ф) = 0 + sin Ф

sin(π - Ф) = sin Ф

9.

∵ cos 2Ф = 2 cos²Ф - 1

∵ cos Ф = [tex]\frac{1}{2}[/tex]

∴ cos 2Ф = 2 ( [tex]\frac{1}{2}[/tex] )² - 1

∴ cos 2Ф = 2 × [tex]\frac{1}{4}[/tex] - 1

∴ cos 2Ф = [tex]\frac{1}{2}[/tex] - 1

cos 2Ф = [tex]-\frac{1}{2}[/tex]

10.

∵ sin 2Ф = 2 sinФ cosФ

∵ cosФ = 0.6 and 0° < Ф < 90°

- That means Ф is in the 1st quadrant and all its trigonometry

   ratios are positive

∵ sin²Ф + cos²Ф = 1

∴ sin²Ф + (0.6)² = 1

∴ sin²Ф + 0.36 = 1

- Subtract 0.36 from both sides

∴ sin²Ф = 0.64

- Take √ for both sides

∴ sinФ = 0.8

- Substitute the values of sinФ and cosФ in the rule above

∴ sin 2Ф = 2(0.8)(0.6)

sin 2Ф = 0.96